Geometallurgy study of the Catalão I Nelsonite bodies aiming to increase the niobium production - Rangel, Leonardo Vasconcellos; Mazzinghy, Douglas Batista; Silva, Gilberto Rodrigues da; Seguin, Felipe; Teixeira, Michelle Fernanda De Lira; Ferreira Junior, Sebastião Ubaldino; Vieira, Caio Henrique Ribeiro; Borges Junior, Wanderson Ferreira; Silva, Vinicius Campos; Dimitrov, Gabriel Rocha (Tecnologia em metalurgia, materiais e mineração, 2020)
Increasing the recovery of the niobium metal contained in the Nelsonite rocks presents a great challenge, considering the standards and the production targets of the China Molybdenum Company (CMOC) that produces phosphate and with tailings material, concentrate niobium minerals. At Chapadão mine, located in Goiás, a mid-west Brazil’s state, the weathering profile reaches up to 100 meters and the ore is subdivided into three basic types, from top to bottom: Oxidized (OX), Top Micaceous (TM) and Base Micaceous (BM). In this study, samples from these three main bodies of Nelsonite were collected and tested in laboratory scale to identify which weathering level is more favourable to niobium concentrate production. In the niobium concentration process, there can be metal losses that can jeopardize the recovery of the niobium crystals. To evaluate these losses microscopy analysis was performed using samples from industrial plant survery. The results from flotation batch tests showed that BM presented the higher mass recovery and production capacity. According to the mineralogical results the main niobium losses were identified in the barite concentrate from apatite circuit and in the screening stage in the Niobium Plant feed. The batch test results showed that adjusting the cut size of the Niobium Plant there is a potential niobium recovery upgraded to 90% from Ba-pyrochlore, and, adding the barite concentrate product as an additional mass in the tailings feed, it will result together in more than 1 t/day of niobium concentrate final product, reducing the losses and utilizing better the ore blend recovery potential.